Metabolic syndrome and cardiovascular risk - Abdullah M Alshehri (Wolters Kluwer Medknow Publications, 2010)
The constellation of dyslipidemia (hypertriglyceridemia and low levels of high-density lipoprotein cholesterol), elevated blood pressure, impaired glucose tolerance, and central obesity is now classified as metabolic syndrome, also called syndrome X. In the past few years, several expert groups have attempted to set forth simple diagnostic criteria for use in clinical practice to identify patients who manifest the multiple components of the metabolic syndrome. These criteria have varied somewhat in specific elements, but in general, they include a combination of multiple and metabolic risk factors. The most widely recognized of the metabolic risk factors are atherogenic dyslipidemia, elevated blood pressure, and elevated plasma glucose. Individuals with these characteristics, commonly manifest a prothrombotic state as well as and a proinflammatory state. Atherogenic dyslipidemia consists of an aggregation of lipoprotein abnormalities including elevated serum triglyceride and apolipoprotein B (apoB), increased small LDL particles, and a reduced level of HDL cholesterol (HDL-C). The metabolic syndrome is often referred to as if it were a discrete entity with a single cause. Available data suggest that it truly is a syndrome, ie, a grouping of atherosclerotic cardiovascular disease (ASCVD) risk factors, that probably has more than one cause. Regardless of cause, the syndrome identifies individuals at an elevated risk for ASCVD. The magnitude of the increased risk can vary according to the components of the syndrome present as well as the other, non-metabolic syndrome risk factors in a particular person.